2004
DOI: 10.1007/s10346-003-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based SAR interferometry for monitoring mass movements

Abstract: An innovative technique for the remote assessment of ground displacements, based on radar interferometry and implemented using ground-based instrumentation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(113 citation statements)
references
References 13 publications
0
110
0
Order By: Relevance
“…Toc (Vajont), Voight (1988) found that rates can be suitably (Fig. 10a) are obtained by Bstacking^the interferograms phase using 8-h averaged SAR images, with a measurement accuracy of ±0.5 mm (Antonello et al 2004;Intrieri et al 2013;Di Traglia et al 2014;Di Traglia et al 2015). Interferometric phase can be corrupted by noise (decorrelation), caused by the contribution of scatterers summing up differently among SAR acquisitions and estimated by a calculation of the Bcoherence^between two images (values in the range 0-1).…”
Section: Effect Of Noise On the Reliability Of T F Predictionsmentioning
confidence: 99%
“…Toc (Vajont), Voight (1988) found that rates can be suitably (Fig. 10a) are obtained by Bstacking^the interferograms phase using 8-h averaged SAR images, with a measurement accuracy of ±0.5 mm (Antonello et al 2004;Intrieri et al 2013;Di Traglia et al 2014;Di Traglia et al 2015). Interferometric phase can be corrupted by noise (decorrelation), caused by the contribution of scatterers summing up differently among SAR acquisitions and estimated by a calculation of the Bcoherence^between two images (values in the range 0-1).…”
Section: Effect Of Noise On the Reliability Of T F Predictionsmentioning
confidence: 99%
“…The displacement is calculated from the phase difference between the back-scattered microwave signals received at different times through the cross-correlation of two SAR images. Images are obtained through sampling techniques, so frequency and spatial steps have to be selected in order to avoid ambiguity in range and cross-range (Antonello et al 2004). At Stromboli, the GBInSAR produces one SAR image of the NE flank of the crater area and of the upper part of the Sciara del Fuoco every 11 min.…”
Section: The Gbinsar Systemmentioning
confidence: 99%
“…Displacements can be estimated with high accuracy by stacking the phase of the interferograms, i.e., by processing many images together rather than adopting a more classic two-image approach. At Stromboli, the GBInSAR combines all the 8-hour-averaged images (Zebker et al 1997;Antonello et al 2004;Intrieri et al 2013a), producing cumulative displacement maps and displacement time series with an accuracy of ±0.5 mm (Di Traglia et al 2014c. Interferometric stacks are useful to highlight persistent deformation, suppressing other random signals, like atmospheric anomalies (Pinel et al 2014).…”
Section: The Gbinsar Systemmentioning
confidence: 99%
“…GB-InSAR is a well-known technique, which has been widely used in deformation monitoring in civil structures and natural phenomena [42][43][44]. Due to its capabilities of offering optimal observing geometry and a significantly high-frequency data acquisition rate, GB-InSAR overcomes the limitations of space-borne DInSAR, such as a fixed revisit cycle and observation angle constraints.…”
Section: Ground-based Radar Interferometry Measurementsmentioning
confidence: 99%